An Overview of the Direct Preparation of Organoaluminum Compounds - Piccardi, Riccardo; Micouin, Laurent (Synthesis, 2025)
Organoaluminum compounds are a unique class of organometallics, valued for their strong Lewis acidity and distinctive reactivity. Since Ziegler’s pioneering work in the mid-20th century, they have become important in catalysis and polymer production, benefiting from aluminum’s abundance, low cost, and low toxicity. However, their use in organic synthesis remains limited due to the complexity of their preparation—typically involving transmetalation steps that often reduce their advantages. Coordinating solvents used in these steps can also suppress the compounds’ Lewis acidity. This review explores alternative, more direct methods of synthesizing organoaluminum compounds and highlights recent progress in this area.
Keywords: Organoaluminum reagents; Carboalumination; Hydroalumination; Metallation; C–H activation; Functional organometallics